The effect of nozzle orifice diameter on penetration depth and mechanical properties of AISI 430/AISI 1040 dissimilar steel joined by keyhole PTA welding process - Teker, T.; Ozdemir, N. (Redakcia Kovove Materialy, 2013)
In this study, AISI 430/AISI 1040 steel couple 10 mm thick were welded in the butt position without any pre-treatment using keyhole plasma transferred arc (KPTA) process. Welded joints were manufactured selecting constant welding speed (0.01 m min(-1)) and two different nozzle orifice diameters (2.4 and 3.2 mm), three different welding currents (130, 135 and 140 A), at a constant plasma gas flow (1.2 l min(-1)), a shielding gas flow (25 l min(-1)). The microstructural changes that occurred in the interface regions of the welded samples were examined by microhardness, scanning electron microscopy (SEM), X-ray diffraction (XRD) and energy dispersive spectrometer (EDS). In order to determine mechanical properties of samples, the V-notch Charpy tests were performed. In addition, fracture types in the notch impact strength tests of samples were determined from the fractographic examinations using SEM.
Keywords: plasma transferred arc welding; keyhole; AISI 430; AISI 1040; nozzle orifice diameter